Creating value from mergers in the South African pharmaceutical industry - Naidoo, Angie Nicole (My University, 2012)
Mergers and acquisitions (M and A's) has become a strategic option for companies to meet the strategic needs of the rapidly changing competitive landscape. Pharmaceutical companies are facing several major inter-related challenges, the most strategic being the decline in Research and Development (R and D) productivity resulting in empty product pipelines which cannot replace the products nearing patent expiry, competition from generics, healthcare costs and product liability. The aim of this study was to identify and describe the drivers of merger success in the pharmaceutical industry in South Africa and the aspects of an effective post-merger value creation strategy that will grow the business and maintain business continuity. Data was collected through conducting 20 semi-structured interviews to search for a deeper understanding of merger and acquisitions in the pharmaceutical industry in South Africa. The main findings in this research have shown that the aspects of an effective postmerger value creation strategy start with a well-articulated plan for integration. Each step of each plan has to be communicated to all stakeholders in a manner that is transparent, open and honest so that there is buy-in, acceptance and finally mobilisation of the company to create the desired value. Pivotal to local companywide post-merger value creation are leaders that are trusted, who will enable the organisation to align around the vision and mission and goals of the merger. Decisions require foresight. Culture underscores the success of any strategy in the organisation. The end goal of achieving post-merger value creation depends on the organisation’s resources, the people, processes and systems; and matching these with the external opportunities. Retaining the best from both legacy organisations and fusing them together will result in a high performance organisation which will create post-merger value. Not much has changed in the industry except for the risks and the size of the opportunities. Strategic alliances with companies that have expertise in health economics and health technology assessments and companies that have strong relationships with authorities, who will register products faster, should be an option for serious consideration for future growth.
MBA thesis - WBS
Keywords: Mergers and acquisitions; Pharmaceutical industry